2010
DOI: 10.1002/micr.20818
|View full text |Cite
|
Sign up to set email alerts
|

Isogenic venous graft supported with bone marrow stromal cells as a natural conduit for bridging a 20 mm nerve gap

Abstract: In this study, we introduce a technique for bridging large neural gaps, using an isogenic vein graft supported with isogenic bone marrow stromal cells (BMSC). In three groups a nerve defect of 20 mm was bridged with a vein graft. Our first experimental group comprized an empty venous graft, in group II the venous nerve graft was filled with saline where as in group III the venous nerve graft was filled with BMSC. The animals were tested for functional recovery up to 3 months post repair. Our results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
1
29
0
3
Order By: Relevance
“…A few examples of these additives uses are nerve growth factor, Schwann cells, and several types of The effect of stem cells in bridging peripheral nerve defects: a meta-analysis stem cells. 4,15,34,36,47,56 A number of different types of stem cells have been used in animal experiments focusing on nerve regeneration in a nerve reconstruction model. Bone marrow stromal cells (BMSCs), adipose-derived stromal cells (ADSCs), hair follicle stem cells, skin-derived mesenchymal stem cells, and amniotic fluid-derived mesenchymal stem cells can all be applied.…”
Section: ©Aans 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…A few examples of these additives uses are nerve growth factor, Schwann cells, and several types of The effect of stem cells in bridging peripheral nerve defects: a meta-analysis stem cells. 4,15,34,36,47,56 A number of different types of stem cells have been used in animal experiments focusing on nerve regeneration in a nerve reconstruction model. Bone marrow stromal cells (BMSCs), adipose-derived stromal cells (ADSCs), hair follicle stem cells, skin-derived mesenchymal stem cells, and amniotic fluid-derived mesenchymal stem cells can all be applied.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…48 Another theory, however, regarding the beneficial effect of BMSCs is that they function as growth promoting factors. 34 ADSCs are less invasive to harvest as they can be derived from belly fat or other adipocyte-containing tissue. They have a comparable phenotypic profile as the BMSCs, and some studies have even indicated that ADSCs have a more profound tendency to transdifferentiate into a Schwann cell-like phenotype.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…Interestingly, however, the positive effects of undifferentiated cells have also been widely reported [5,7,13,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] . These investigators claim that in vitro differentiation incurs an unnecessary delay, limiting clinical applicability.…”
Section: Differentiationmentioning
confidence: 99%
“…Under appropriate conditions BMSCs can differentiate into non-mesodermal lineages such as neurons, astrocytes and SC-like cells [90] . Many studies have shown that the addition of BMSCs to conduits and acellular grafts results in superior outcomes when compared with empty or cell deplete channels [24,[36][37][38]40,41] . Although some have failed to show that BMSCs can match outcomes achieved with cultured SCs [20] , the majority of reports show that performance is at least equivalent [27,43,91] .…”
Section: Bone Marrow Derived Stem Cellsmentioning
confidence: 99%
“…The vein as a natural replacement was already promoted in 1982 by Chiu et al [ 9 ]. In 2010 we showed that vein grafts are more abundantly available in a wide variety of sizes and lengths, have minimal donor morbidity, and provide a metabolically supportive environment for the regenerating axons [ 5 ]. Zhang et al demonstrated that the wall of the vein has an additional advantage providing a barrier against scar ingrowth [ 10 ].…”
Section: Vein Graftmentioning
confidence: 98%